Expression of cholinesterases in human kidney and its variation in renal cell carcinoma types - Muñoz-Delgado, Encarnación; Montenegro, María Fernanda; Campoy, Francisco Javier; Moral-Naranjo, María Teresa; Cabezas-Herrera, Juan; Kovacs, Gyula; Vidal, Cecilio J. (The FEBS journal, 2010)
Despite the aberrant expression of cholinesterases in tumours, the question of their possible contribution to tumorigenesis remains unsolved. The identification in kidney of a cholinergic system has paved the way to functional studies, but details on renal cholinesterases are still lacking. To fill the gap and to determine whether cholinesterases are abnormally expressed in renal tumours, paired pieces of normal kidney and renal cell carcinomas (RCCs) were compared for cholinesterase activity and mRNA levels. In studies with papillary RCC (pRCC), conventional RCC, chromophobe RCC, and renal oncocytoma, acetylcholinesterase activity increased in pRCC (3.92 ± 3.01 mU·mg−1, P = 0.031) and conventional RCC (2.64 ± 1.49 mU·mg−1, P = 0.047) with respect to their controls (1.52 ± 0.92 and 1.57 ± 0.44 mU·mg−1). Butyrylcholinesterase activity increased in pRCC (5.12 ± 2.61 versus 2.73 ± 1.15 mU·mg−1, P = 0.031). Glycosylphosphatidylinositol-linked acetylcholinesterase dimers and hydrophilic butyrylcholinesterase tetramers predominated in control and cancerous kidney. Acetylcholinesterase mRNAs with exons E1c and E1e, 3′-alternative T, H and R acetylcholinesterase mRNAs and butyrylcholinesterase mRNA were identified in kidney. The levels of acetylcholinesterase and butyrylcholinesterase mRNAs were nearly 1000-fold lower in human kidney than in colon. Whereas kidney and renal tumours showed comparable levels of acetylcholinesterase mRNA, the content of butyrylcholinesterase mRNA was increased 10-fold in pRCC. The presence of acetylcholinesterase and butyrylcholinesterase mRNAs in kidney supports their synthesis in the organ itself, and the prevalence of glycosylphosphatidylinositol-anchored acetylcholinesterase explains the splicing to acetylcholinesterase-H mRNA. The consequences of butyrylcholinesterase upregulation for pRCC growth are discussed. Structured digital abstract • MINT-7992181: BuChE (uniprotkb:P06276) and BuChE (uniprotkb:P06276) bind (MI:0407) by chromatography technology (MI:0091) • MINT-7992175: AChE (uniprotkb:P22303) and AChE (uniprotkb:P22303) bind (MI:0407) by chromatography technology (MI:0091)